Developing a meaningful chemistry learning environment in cooperation with industry - Ikävalko, Veli-Matti (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
Learning environments outside of the classroom, context-based and a meaningful learning of chemistry are central themes in the new core curricula for basic education. Research-based approaches are needed in order to support these. This article introduces a design-based research in progress, where the aim is to develop the university laboratory ChemistryLab Gadolin into a meaningful visiting and learning environment with producing new context-based work instructions. Instructions have been produced in cooperation with companies, specialists and chemistry teacher students.